Perindopril metabolic effects and organo-protective action in metabolic syndrome patients - V. B. Mychka; V. P. Masenko; N. V. Flegontova; D. M. Ataullakhanova; V. B. Sergienko; I. E. Chazova (Кардиоваскулярная терапия и профилактика)
Aim. To assess perindopril antihypertensive effects and its influence on metabolic disturbances, myocardial structure, and cerebral perfusion (CP) in patients with mild to moderate arterial hypertension (AH) and metabolic syndrome (MS) (AH + MS). Material and methods. Thirty patients with mild to moderate AH + MS participated in the study. At baseline and 24 weeks later, 24-hour blood pressure monitoring (BPM), carbohydrate and lipid metabolism, insulin sensitivity, myocardial structure and function, as well as CP parameters were assessed. Results. Target BP levels were achieved in 70% of the patients receiving perindopril: 9 and 21 patients were administered 4 and 8 mg/d, respectively. Fasting and postprandial glucose levels decreased significantly (both p<0,05). Insulin sensitivity index (Si) increased from 0,5 х 10-4 min-1(mcUml)-1 to 1,3 х 10-4 min-1(mcUml)-1 (р<0,05). High-density lipoprotein cholesterol (HDL-CH) level increased significantly (p<0,05). Initially reduced CP substantially improved. In all participants, perindopril therapy resulted in regressed left ventricular (LV) hypertrophy and improved LV geometry. Conclusion. Perindopril demonstrates good antihypertensive effect, improved carbohydrate and lipid metabolism, as well as tissue insulin sensitivity, CP, LV structure and function in AH + MS patients.